DAMPAK NEGATIF PENGGUNAAN GADGET DI KALANGAN REMAJA GEREJA MANDIRI PROTESTAN KORAMPOTAN PONDAN: DAMPAK NEGATIF PENGGUNAAN GADGET DI KALANGAN REMAJA GEREJA MANDIRI PROTESTAN KORAMPOTAN PONDAN - Abriani Maong; Experius Djaka; Arnold Sumaa (APOSTOLOS, 2022)
The development of technology is currently growing rapidly, thus making teenagers want to have a gadget. it is unavoidable that the presence of gadgtes has a major influence on the character of teenagers. Where during worship,teenagers us gadgets to open facebook, WhatsApp, and play games. The purpose of the study was to describe the negative use of gadgets among adolescents at the Korampotan Pondan Protestant Independent CWith the research subject is an independent youth Protestan Korampotan Pondan. This sudy aims to determine the effect of teenagers in the Independen Protestan Church of Korampotan Pondan. The method used is a quantitative method with a population of 75 people, a sample of 43 people, with data collection techniques using questionnaires